Healthy eating index and sodium/(potassium+calcium) indicator in Chilean university students - Maury-Sintjago, Eduard; Rodríguez-Fernández, Alejandra; Parra-Flores, Julio (Universidad y Salud, 2020)
Introducción: Unhealthy eating habits of university students constitutes an important concern for future medical and nutritional care. Objective: To determine the Healthy Eating Index (HEI) and the sodium/(potassium+calcium) indicator in Chilean university students. Materials and methods: An analytical cross-sectional research was carried out with a non-probabilistic sample of 420 students, who answered a survey covering sociodemographic and anthropometric issues. The HEI and sodium/(potassium+calcium) indicator were determined using the consumption frequency and 24-hour reminder questionnaire. A descriptive and inferential statistical analysis was applied through the SPSS (v22.0) program. Results: The weight, height and the body mass index (BMI) of the participants showed statistically significant differences according to their gender (p<0.05). A similar pattern was found in the average intake of calories, lipids, carbohydrates, fiber, calcium and sodium (p<0.05). Intake of fruits, vegetables and low-fat dairy products was higher in women (p<0.01). The majority of participating students had an unhealthy diet, with the situation being more severe in men (p<0.05). Only 6% of men and 17% of women had a cardio-protective diet. Conclusions: Students follow diets with a deficient intake of cardio-protective micronutrients, which increases the risk of developing cardiovascular diseases.